2013
DOI: 10.31729/jnma.2282
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Ameloblastoma of the Mandible

Abstract: The Desmoplastic Ameloblastoma exhibits important differences in anatomical distribution, histologicappearance and radiographic findings compared with the classic type of ameloblastoma. We describea case of desmoplastic variant of ameloblastoma localized in the mandibular anterior portion of thejaw, extending posteriorly in the left side. The tumor was expansile, slowly growing and painless.The radiographic finding showed diffuse, radiolucent lesion with cortical bone expansion. Surgicalexcision was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Instead, this area appears hypercellular and is composed of spindle-shaped or polygonal epithelial cells. [ 20 21 22 ] Similar features were observed in our study wherein basal cell palisading with reversal of polarity and subnuclear vacuolization was not observed in any of the cases studied. The characteristic histopathological features of ameloblastoma will be masked in desmoplastic ameloblastoma because of extensive stromal desmoplasia which constricts the typical ameloblastic follicles.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, this area appears hypercellular and is composed of spindle-shaped or polygonal epithelial cells. [ 20 21 22 ] Similar features were observed in our study wherein basal cell palisading with reversal of polarity and subnuclear vacuolization was not observed in any of the cases studied. The characteristic histopathological features of ameloblastoma will be masked in desmoplastic ameloblastoma because of extensive stromal desmoplasia which constricts the typical ameloblastic follicles.…”
Section: Discussionsupporting
confidence: 86%
“…and the expansion of the involved bone is the commonly observed clinical manifestations. [ 9 ] In our case, the location of the lesion was in the mandibular anterior front tooth region also involving left lateral incisor to left second premolar region, clinical signs and symptoms like pain and discharge were absent.…”
Section: Discussionmentioning
confidence: 63%
“…In a review of 115 cases of DAs, the commonly observed radiographical features were mixed radiolucent/radiopaque (56%), multilocular (49%), and with ill-defined borders (64%). [ 9 ] In this case, multilocular radiolucency with radio-opaque areas was observed in the mandibular anterior region.…”
Section: Discussionmentioning
confidence: 77%